Anticorrosive paint as well as preparation method and application thereof

By using anticorrosion coatings prepared by using epoxy resin, modified graphene oxide, sea buckthorn powder and chelating agent, the problem of poor weather resistance of existing coatings in high salt spray and high humidity environments is solved, and long-term anticorrosion performance and significant service life are achieved.

CN119859458APending Publication Date: 2025-04-22CHINA COMMUNICATIONS COMMUNICATIONS SECOND AVIATION ADMINISTRATION JILIN CONSTRUCTION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411927928.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing anticorrosion coatings have poor weather resistance in high salt spray and high humidity environments, high cost and complex maintenance, making it difficult to achieve long-term stable anticorrosion effect.

Method used

Anticorrosion coatings are prepared by epoxy resin, modified graphene oxide, sea buckthorn powder and chelating agent. The dispersion and corrosion resistance of the coating are improved through the preparation method of modified graphene oxide and the selection of chelating agents.

Benefits of technology

It achieves long-term anti-corrosion performance in high salt spray and high humidity environments, with water resistance of more than 230 hours and salt spray resistance of more than 1100 hours, significantly extending the service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209659930000061
    Figure BDA0005209659930000061
  • Figure BDA0005209659930000071
    Figure BDA0005209659930000071
  • Figure BDA0005209659930000081
    Figure BDA0005209659930000081
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, and particularly discloses an anticorrosive coating as well as a preparation method and application thereof. The anticorrosive coating provided by the invention comprises the following components in parts by weight: 60-80 parts of epoxy resin, 5-12 parts of modified graphene oxide, 6-8 parts of a curing agent, 5-10 parts of sea-buckthorn powder, 3-5 parts of a chelating agent, 5-10 parts of filler and 1-3 parts of other auxiliaries, furthermore, the anticorrosive paint comprises the following components in parts by weight: 60-80 parts of epoxy resin, 8-10 parts of modified graphene oxide, 6-8 parts of a curing agent, 6-8 parts of sea-buckthorn powder, 3-5 parts of a chelating agent, 5-10 parts of filler and 1-3 parts of other auxiliaries. Wherein the modified graphene oxide is obtained by modifying graphene oxide with phosphoric acid. The anticorrosive paint provided by the invention has good weather resistance and corrosion resistance, and can realize long-acting protection under severe environmental conditions of high humidity and high salt mist when being applied to the surface of a wind generating set component.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coating technology, and in particular to an anti-corrosion coating and a preparation method and application thereof. Background Art

[0002] With the growth of global energy demand and the improvement of environmental awareness, wind energy has been widely used and developed as a clean and sustainable energy source. Wind power generation can not only reduce the consumption of fossil fuels, but also effectively reduce greenhouse gas emissions, which is of great significance to promoting environmental protection and sustainable development. However, wind turbines face various environmental challenges in actual operation, especially in coastal and high humidity areas. Salt spray corrosion has become one of the main factors affecting the reliability and service life of wind turbines. This corrosion not only damages the appearance of wind turbines, but also may cause damage to the internal structure, thus affecting the normal operation and safety of the entire system.

[0003] In order to solve the corrosion problem of wind turbines in coastal and high-humidity areas, the industry has developed a variety of protective measures. The traditional method is to use organic coating materials to form a dense protective film on the metal surface to isolate the external environment and prevent moisture and salt from directly contacting the metal surface. In recent years, studies have reported a cathodic protection technology that uses sacrificial anodes or applied current to put the protected body in a negative potential state, thereby achieving an anti-corrosion effect.

[0004] Although the above methods can alleviate the corrosion problem of wind turbines to a certain extent, there are still some problems. The weather resistance of traditional organic coatings is poor. Long-term exposure to salt spray and moisture will cause the protective film to gradually fail and cannot resist corrosion permanently. Although cathodic protection technology has a good anti-corrosion effect, it is expensive and requires regular maintenance and replacement of anodes or adjustment of power settings, which is more complicated to operate. Therefore, how to develop an economical and efficient anti-corrosion material to adapt to the long-term stable operation of wind turbines in harsh environments has become a key issue that needs to be solved urgently. Summary of the invention

[0005] In order to overcome the problems of high cost and poor long-term anti-corrosion effect of existing anti-corrosion coatings, the present application provides an anti-corrosion coating and a preparation method and application thereof.

[0006] In the first aspect, the present application provides an anti-corrosion coating, which adopts the following technical solution: An anticorrosive coating comprises the following components in parts by weight: 60-80 parts of epoxy resin, 5-12 parts of modified graphene oxide, 6-8 parts of curing agent, 5-10 parts of seabuckthorn powder, 3-5 parts of chelating agent, 5-10 parts of filler, and 1-3 parts of other additives; Wherein, the preparation method of the modified graphene oxide comprises the following steps: (1) dispersing graphene oxide in water and ultrasonically dispersing the water to obtain a graphene oxide solution; (2) adding a phosphoric acid solution to the graphene oxide solution, dispersing by ultrasonication, and then stirring and reacting at 60-80° C. for 10-12 hours to obtain a mixed solution; The concentration of the graphene oxide solution is 3-5 g / L, the concentration of the phosphoric acid solution is 60-70 wt %, and the volume ratio of the graphene oxide solution to the phosphoric acid solution is 10:(2.5-5); (3) adding water to the mixed solution, stirring evenly, and performing solid-liquid separation and freeze-drying to obtain modified graphene.

[0007] The present application adopts epoxy resin, modified graphene oxide sea buckthorn powder and chelating agent to prepare an anti-corrosion coating, which has excellent weather resistance and corrosion resistance. The anti-corrosion coating is used on the surface of wind turbine components. On the one hand, it can isolate the contact between the construction surface and the external environment, and effectively prevent the corrosion of wind turbine components in harsh environmental conditions of high salt fog and high humidity; on the other hand, the anti-corrosion coating can also transform or transfer rust on the surface of the component into the coating, further improving the corrosion resistance of the component.

[0008] In the present application, epoxy resin is the main component, which has good adhesion and mechanical strength, and can firmly adhere to the metal surface to form a dense protective layer; and the polymer structure of epoxy resin can effectively block the penetration of moisture and oxygen, further enhancing the anti-corrosion effect of the coating; graphene oxide has a unique two-dimensional structure, which can form a tight barrier on the surface of the component, effectively preventing moisture, oxygen and corrosive substances from contacting the metal component; in addition, the present application uses phosphoric acid to modify graphene oxide, which can enhance the dispersibility of graphene oxide in the coating, reduce defects such as micropores or microcracks in the coating, and enable the coating to maintain stable protective performance for a long time. Seabuckthorn powder is rich in natural polyphenol compounds, which have strong antioxidant and metal ion chelating effects. It can complex with iron ions on the metal surface, which can reduce the active points on the metal surface and inhibit the occurrence of corrosion reactions. On the other hand, polyphenol compounds can complex with iron ions to form dense network complexes, which can be well attached to the surface of metal components and closely combined with the metal component matrix, thereby isolating the metal surface from contact with external moisture, oxygen and corrosive substances, and playing a good anti-rust and anti-corrosion role. Chelating agents can react with rust generated on the surface of metal components, and convert rust into stable substances or transfer them to anti-corrosion coatings, converting them into part of the coating, improving the density of the coating, and further improving the corrosion resistance of metal components. In summary, this application prepares anti-corrosion coatings by using the above-mentioned substances, and controls the addition amount of each component within the above-mentioned range. The obtained anti-corrosion coating has excellent corrosion resistance. It is used on the surface of wind turbine components to achieve effective protection of components. Even in extreme environments such as high humidity and salt spray, it can maintain long-term anti-corrosion performance and significantly extend the service life of the equipment.

[0009] In some embodiments, the volume ratio of the graphene oxide solution to the phosphoric acid solution can be 10:(2.5-3), 10:(2.5-4), 10:(2.5-5), 10:(3-4), 10:(3-5) or 10:(4-5).

[0010] In a specific embodiment, the volume ratio of the graphene oxide solution to the phosphoric acid solution can also be 10:2.5, 10:3, 10:4 or 10:5.

[0011] In some embodiments, the weight parts of the modified graphene oxide may be 5-8 parts, 5-10 parts, 5-12 parts, 8-10 parts, 8-12 parts or 10-12 parts.

[0012] In a specific embodiment, the weight parts of the modified graphene oxide can also be 5 parts, 8 parts, 10 parts or 12 parts.

[0013] In some embodiments, the weight portion of the seabuckthorn powder may be 5-6 parts, 5-8 parts, 5-10 parts, 6-8 parts, 6-10 parts or 8-10 parts.

[0014] In a specific embodiment, the weight portion of the seabuckthorn powder can also be 5 parts, 6 parts, 8 parts or 10 parts.

[0015] In some embodiments, the weight portion of the chelating agent may be 3-4 parts or 4-5 parts.

[0016] In a specific embodiment, the weight portion of the chelating agent can also be 3 parts, 4 parts or 5 parts.

[0017] Optionally, the volume ratio of the graphene oxide solution to the phosphoric acid solution is 10:(3-4).

[0018] Optionally, the ultrasonic dispersion has a power of 80-100 W and a time of 5-10 min.

[0019] Optionally, the anti-corrosion coating comprises the following components in parts by weight: 60-80 parts of epoxy resin, 8-10 parts of modified graphene oxide, 6-8 parts of curing agent, 6-8 parts of sea buckthorn powder, 3-5 parts of chelating agent, 5-10 parts of filler, and 1-3 parts of other additives.

[0020] In the present application, the addition amount of modified graphene oxide, sea buckthorn powder and chelating agent in the anti-corrosion coating will affect the water resistance and salt spray resistance of the anti-corrosion coating; through experimental research, the present application found that by further controlling the addition amount of each component in the anti-corrosion coating within the above-mentioned range, the anti-corrosion performance of the obtained anti-corrosion coating is better, and its water resistance can reach more than 230 hours, and its salt spray resistance can reach more than 1100 hours.

[0021] Optionally, the chelating agent is selected from one or more of glycolic acid, benzohydroxamic acid, citric acid, tetrasodium iminodisuccinate, potassium thiocyanate and disodium ethylenediaminetetraacetate.

[0022] Optionally, the chelating agent is a mixture of glycolic acid, benzohydroxamic acid and potassium thiocyanate.

[0023] Optionally, the weight ratio of glycolic acid, benzohydroxamic acid and potassium thiocyanate is 2:(0.35-0.65):(0.5-0.8).

[0024] In this application, glycolic acid has a strong chelating effect, which can effectively capture metal ions in rust and remove rust without destroying the steel substrate; the structure of benzohydroxamic acid contains a benzene ring, a hydroxyl group (OH) and an oxime group (C=NOH), and this unique structure gives it a strong complexing ability. Benzohydroxamic acid can form a stable complex with iron ions to improve the weather resistance and anti-aging ability of the coating; potassium thiocyanate can form a stable iron thiocyanate complex with iron ions through coordination, and the iron thiocyanate complex can be transferred to the coating to improve the compactness of the coating and further improve the corrosion resistance of metal components. This application has found through experimental exploration that further using glycolic acid, benzohydroxamic acid and potassium thiocyanate as chelating agents, and controlling the ratio of the three within the above range, can effectively improve the stability and anti-corrosion performance of the coating, and the synergistic effect of these three components enables the coating to maintain excellent anti-corrosion performance under long-term exposure to salt spray and moisture, which is suitable for long-term protection of wind turbine components.

[0025] In some embodiments, the weight ratio of glycolic acid, benzohydroxamic acid and potassium thiocyanate can be 2:(0.35-0.5):0.7, 2:(0.5-0.65):0.7, 2:0.5:(0.5-0.7) or 2:0.5:(0.7-0.8).

[0026] In a specific embodiment, the weight ratio of glycolic acid, benzohydroxamic acid and potassium thiocyanate can also be 2:0.5:0.7, 2:0.35:0.7, 2:0.65:0.7, 2:0.5:0.5 or 2:0.5:0.8.

[0027] Optionally, the curing agent is an amine curing agent; the filler is silicon dioxide and / or zinc phosphate; and the other auxiliary agents are selected from one or more of a dispersant, a leveling agent and a wetting agent.

[0028] In the second aspect, the present application provides a method for preparing an anti-corrosion coating, comprising the following steps: first, dispersing modified graphene oxide, a chelating agent, sea buckthorn powder and a filler in water, and then adding epoxy resin and mixing evenly to obtain material A; mixing other additives and a curing agent evenly to obtain material B; mixing material A and material B evenly to obtain an anti-corrosion coating.

[0029] Optionally, the wind turbine component is a wind turbine blade.

[0030] In summary, this application has the following beneficial effects: 1. The present application adopts epoxy resin, modified graphene oxide, sea buckthorn powder and chelating agent to prepare an anti-corrosion coating, the water resistance of the anti-corrosion coating is 208-294h, and the salt spray resistance is 1027-1283h. Applying the above anti-corrosion coating on the surface of steel can form a protective film on the surface of steel, thereby preventing the steel from contacting with moisture, oxygen and corrosive substances in the external environment, thereby effectively improving the corrosion resistance of steel.

[0031] 2. In the present application, the addition amount of modified graphene oxide, sea buckthorn powder and chelating agent in the anti-corrosion coating is further controlled within the following range: 8-10 parts of modified graphene oxide, 6-8 parts of sea buckthorn powder and 3-5 parts of chelating agent. The water resistance of the obtained anti-corrosion coating is greater than 230h and the salt spray resistance is greater than 1100h.

[0032] 3. The present application adopts a mixture of hydroxyacetic acid, benzohydroxamic acid and potassium thiocyanate as a chelating agent, and controls the weight ratio of the three within the range of 2: (0.35-0.65): (0.5-0.8). The anti-corrosion coating obtained has better anti-corrosion performance, with water resistance > 280h and salt spray resistance > 1250h. DETAILED DESCRIPTION

[0033] The present application provides an anti-corrosion coating, comprising the following components in parts by weight: 60-80 parts of epoxy resin, 5-12 parts of modified graphene oxide, 6-8 parts of curing agent, 5-10 parts of sea buckthorn powder, 3-5 parts of chelating agent, 5-10 parts of filler, and 1-3 parts of leveling agent; further, the anti-corrosion coating comprises the following components in parts by weight: 60-80 parts of epoxy resin, 8-10 parts of modified graphene oxide, 6-8 parts of curing agent, 6-8 parts of sea buckthorn powder, 3-5 parts of chelating agent, 5-10 parts of filler, and 1-3 parts of leveling agent.

[0034] Wherein, the chelating agent is selected from one or more of glycolic acid, benzohydroxamic acid, citric acid, tetrasodium iminodisuccinate, potassium thiocyanate and disodium ethylenediaminetetraacetate. Further, the chelating agent is a mixture of glycolic acid, benzohydroxamic acid and potassium thiocyanate; further, the weight ratio of glycolic acid, benzohydroxamic acid and potassium thiocyanate is 2: (0.35-0.65): (0.5-0.8).

[0035] The preparation method of the modified graphene oxide comprises the following steps: (1) dispersing graphene oxide in water, and ultrasonically dispersing for 5-10 min at a power of 80-100 W to obtain a graphene oxide solution; (2) adding a phosphoric acid solution to the graphene oxide solution, ultrasonically dispersing the solution at a power of 80-100 W for 5-10 min, and then stirring the solution at 60-80° C. for 10-12 h to obtain a mixed solution; The concentration of the graphene oxide solution is 3-5 g / L, the concentration of the phosphoric acid solution is 60-70 wt %, and the volume ratio of the graphene oxide solution to the phosphoric acid solution is 10:(2.5-5); further, the volume ratio of the graphene oxide solution to the phosphoric acid solution is 10:(3-4); (3) adding water to the mixed solution, stirring evenly, and performing solid-liquid separation and freeze-drying to obtain modified graphene.

[0036] The preparation method of the anti-corrosion coating provided in the present application comprises the following steps: firstly, dispersing modified graphene oxide, chelating agent, sea buckthorn powder and filler in water, then adding epoxy resin and mixing evenly to obtain material A; mixing other additives and curing agent evenly to obtain material B; mixing material A and material B evenly to obtain the anti-corrosion coating.

[0037] In the present application, the epoxy resin is bisphenol A epoxy resin; graphene oxide is purchased from Yuanye Biotechnology with the product number S25040; the curing agent is BD11 high-temperature epoxy curing agent; sea buckthorn powder is extracted from sea buckthorn fruit and purchased from Fufeng Snow Biotechnology Co., Ltd.; the CAS number of hydroxyacetic acid is 79-14-1; the CAS number of benzohydroxamic acid is 495-18-1; the CAS number of citric acid is 77-92-9; the CAS number of potassium thiocyanate is 333-20-0; the CAS number of disodium ethylenediaminetetraacetic acid is 6381-92-6; the filler is silicon dioxide with a particle size of 30-50nm; the leveling agent is TEGO Glide410; the raw materials, reagents, solvents, etc. used in this application can all be obtained commercially.

[0038] The present application is further described in detail below in combination with preparation examples, embodiments, and performance testing experiments.

[0039] Preparation Example 1-5 Preparation Examples 1-5 each provide a modified graphene oxide.

[0040] The difference between the above preparation examples is that the volume ratio of the graphene oxide solution to the phosphoric acid solution is specifically shown in Table 1 below.

[0041] The preparation method of the modified graphene oxide provided in Preparation Example 1-5 comprises the following steps: (1) dispersing graphene oxide in water and ultrasonically dispersing for 10 min at a power of 100 W to obtain a 4 g / L graphene oxide solution; (2) adding 65 wt % phosphoric acid solution to 4 g / L graphene oxide solution, ultrasonically dispersing at a power of 100 W for 10 min, and then stirring and reacting at 80° C. for 10 h to obtain a mixed solution; the volume ratio of the graphene oxide solution to the phosphoric acid solution is shown in Table 1; (3) adding an equal volume of water to the mixed solution, stirring evenly, and performing solid-liquid separation and solid-phase freeze-drying to obtain modified graphene.

[0042] Table 1 Volume ratio of graphene oxide solution to phosphoric acid solution in Preparation Examples 1-5 Preparation Example Volume ratio of graphene oxide solution to phosphoric acid solution 1 10:2.5 2 10:3 3 10:3.5 4 10:4 5 10:5 Examples 1-5 Embodiments 1-5 respectively provide an anti-corrosion coating.

[0043] The difference between the above embodiments is that the modified graphene oxide in the anti-corrosion coating is derived from Preparation Examples 1-5 respectively.

[0044] The preparation method of the anti-corrosion coating provided in Examples 1-5 comprises the following steps: first, 8 g of modified graphene oxide, 4 g of chelating agent (hydroxyacetic acid), 6 g of sea buckthorn powder and 5 g of filler (silicon dioxide) are dispersed in water, and then 70 g of epoxy resin is added and mixed evenly to obtain material A; 2 g of leveling agent and 7 g of curing agent are mixed evenly to obtain material B; material A and material B are mixed evenly to obtain an anti-corrosion coating.

[0045] Embodiment 6-13 Embodiments 6-13 respectively provide an anti-corrosion coating.

[0046] The difference between the above embodiment and embodiment 3 is that the addition amounts of modified graphene oxide, seabuckthorn powder and chelating agent are specifically shown in Table 2 below.

[0047] Table 2 Addition amount of modified graphene oxide, seabuckthorn powder and chelating agent in Example 3, Examples 6-13 Examples 14-24 Examples 14-24 each provide an anti-corrosion coating.

[0048] The difference between the above embodiment and embodiment 3 is: the type and ratio of the chelating agent, as shown in Table 3 below.

[0049] Table 3 Types and ratios of chelating agents in Example 3 and Examples 14-24 Comparative Example 1 Comparative Example 1 provides an anti-corrosion coating.

[0050] The difference between the above comparative example and Example 3 is that the modified graphene oxide in the anti-corrosion coating is replaced by graphene oxide.

[0051] Comparative Example 2 Comparative Example 2 provides an anti-corrosion coating.

[0052] The difference between the above comparative example and Example 3 is that the amount of modified graphene oxide added to the anti-corrosion coating is 0.

[0053] Comparative Example 3 Comparative Example 3 provides an anti-corrosion coating.

[0054] The difference between the comparative example and Example 3 is that the amount of seabuckthorn powder added to the anti-corrosion coating is 0.

[0055] Comparative Example 4 Comparative Example 4 provides an anti-corrosion coating.

[0056] The difference between the comparative example and Example 3 is that the amount of chelating agent added to the anti-corrosion coating is 0.

[0057] Performance testing The anticorrosive coatings provided in Examples 1-24 and Comparative Examples 1-4 were applied to the surface of the steel sample and cured to form a coating film with a thickness of 200±10 μm. The water resistance and salt spray resistance of the steel sample surface were then tested. The results are shown in Table 4. The test method for water resistance refers to GB / T1722-1993; the test method for salt spray resistance refers to GB / T1771-91.

[0058] Table 4 Corrosion resistance test results of the anticorrosive coatings provided by Examples 1-24 and Comparative Examples 1-4 According to the test results in Table 4, the water resistance of the anticorrosive coating provided in Examples 1-24 is 208-294h, and the salt spray resistance is 1027-1283h; while the water resistance of the anticorrosive coating provided in Comparative Examples 1-4 is 152-187h, and the salt spray resistance is 8113-906h. Therefore, it is shown that the anticorrosive coating prepared by the epoxy resin, modified graphene oxide, sea buckthorn powder and chelating agent in the present application has good anticorrosion performance, and can be used for wind turbine components exposed to salt spray and moisture for a long time, achieving good long-term protection.

[0059] The test results of Examples 1-5 and Comparative Example 1 show that the water resistance of the anticorrosive coating prepared by phosphoric acid-modified graphene oxide in Examples 1-5 of the present application is 213-246h, and the salt spray resistance is 1048-1184h; while the water resistance of the anticorrosive coating prepared by graphene oxide in Comparative Example 1 is only 187h, and the salt spray resistance is only 906h, indicating that phosphoric acid modification of graphene oxide can improve the dispersibility of graphene oxide in the coating, thereby improving the anticorrosion performance of the coating. Further comparison shows that the water resistance of the anticorrosive coating prepared in Examples 2-4 is 235-246h, and the salt spray resistance is 1115-1184h (≥1100h), indicating that the present application further controls the volume ratio of graphene oxide solution to phosphoric acid solution within the range of 10: (3-4), and the corrosion resistance of the obtained anticorrosive coating is better.

[0060] The test results of Example 3 and Example 6-12 show that the water resistance of the anticorrosive coating obtained in Example 3, Example 7-8, Example 10, and Example 12-13 is 237-247h, and the salt spray resistance is 1139-1184h; the water resistance of the anticorrosive coating obtained in Example 6, Example 8-9, and Example 11 is 208-225h, and the salt spray resistance is 1027-1084h. Therefore, considering the comprehensive economic cost, the application further controls the addition amount of modified graphene oxide, sea buckthorn powder and chelating agent in the anticorrosive coating within the following range: 8-10 parts of modified graphene oxide, 6-8 parts of sea buckthorn powder, and 3-5 parts of chelating agent, and the obtained anticorrosive coating has better anticorrosive performance, and its water resistance is greater than 230h, and its salt spray resistance is greater than 1100h.

[0061] The test results of Examples 3 and 14-24 show that Examples 3 and 14-17 use glycolic acid, benzohydroxamic acid, potassium thiocyanate, citric acid or disodium ethylenediaminetetraacetic acid as chelating agents, and the water resistance of the prepared anti-corrosion coating is 209-246h and the salt spray resistance is 1033-1184h; Examples 23-24 use glycolic acid, citric acid and potassium thiocyanate in a weight ratio of 2:0.5:0.7 or glycolic acid, benzyl hydroxamic acid in a weight ratio of 2:0.5:0.7. Hydroxamic acid and disodium ethylenediaminetetraacetic acid are used as chelating agents, and the water resistance of the anticorrosive coating obtained is 253-268h, and the salt spray resistance is 1213-1225h; while Examples 18-22 use hydroxyacetic acid, benzohydroxamic acid and potassium thiocyanate in a weight ratio of 2: (0.35-0.65): (0.5-0.8) as chelating agents, and the water resistance of the anticorrosive coating obtained is 281-294h (> 280h), and the salt spray resistance is 1258-1283h (> 1250h). Therefore, it is explained that the present application uses a mixture of hydroxyacetic acid, benzohydroxamic acid and potassium thiocyanate as a chelating agent, and controls the weight ratio of the three within the range of 2: (0.35-0.65): (0.5-0.8), and the anticorrosive performance of the anticorrosive coating obtained is better.

[0062] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. An anti-corrosion coating, characterized in that: The invention comprises the following components in parts by weight: 60-80 parts of epoxy resin, 5-12 parts of modified graphene oxide, 6-8 parts of curing agent, 5-10 parts of seabuckthorn powder, 3-5 parts of chelating agent, 5-10 parts of filler and 1-3 parts of other auxiliary agents; Wherein, the preparation method of the modified graphene oxide comprises the following steps: (1) dispersing graphene oxide in water and ultrasonically dispersing the graphene oxide to obtain a graphene oxide solution; (2) adding a phosphoric acid solution to the graphene oxide solution, dispersing the solution by ultrasonication, and then stirring the solution at 60-80° C. for 10-12 hours to obtain a mixed solution; The concentration of the graphene oxide solution is 3-5 g / L, the concentration of the phosphoric acid solution is 60-70 wt %, and the volume ratio of the graphene oxide solution to the phosphoric acid solution is 10:(2.5-5); (3) Add water to the mixed solution, stir evenly, separate the solid and liquid, and freeze-dry to obtain modified graphene.

2. The anticorrosive coating according to claim 1, characterized in that: The volume ratio of the graphene oxide solution to the phosphoric acid solution is 10:(3-4).

3. The anticorrosive coating according to claim 1, characterized in that: The power of the ultrasonic dispersion is 80-100W, and the time is 5-10min.

4. The anticorrosive coating according to claim 1, characterized in that: The anticorrosive coating comprises the following components in parts by weight: 60-80 parts of epoxy resin, 8-10 parts of modified graphene oxide, 6-8 parts of curing agent, 6-8 parts of sea buckthorn powder, 3-5 parts of chelating agent, 5-10 parts of filler and 1-3 parts of other additives.

5. The anticorrosive coating according to claim 1, characterized in that: The chelating agent is selected from one or more of glycolic acid, benzohydroxamic acid, citric acid, tetrasodium iminodisuccinate, potassium thiocyanate and disodium ethylenediaminetetraacetate.

6. The anticorrosive coating according to claim 1, characterized in that: The chelating agent is a mixture of glycolic acid, benzohydroxamic acid and potassium thiocyanate.

7. The anticorrosive coating according to claim 6, characterized in that: The weight ratio of the glycolic acid, benzohydroxamic acid and potassium thiocyanate is 2: (0.35-0.65): (0.5-0.8).

8. The anticorrosive coating according to claim 1, characterized in that: The curing agent is an amine curing agent; the filler is silicon dioxide and / or zinc phosphate; and the other auxiliary agents are selected from one or more of a dispersant, a leveling agent and a wetting agent.

9. The method for preparing the anticorrosive coating according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: firstly, dispersing modified graphene oxide, a chelating agent, sea buckthorn powder and a filler in water, then adding epoxy resin and mixing evenly to obtain material A; evenly mixing other auxiliary agents and a curing agent to obtain material B; and evenly mixing material A and material B to obtain an anti-corrosion coating.

10. Application of the anticorrosive coating according to any one of claims 1 to 8 in wind turbine components, characterized in that: The wind turbine component is a wind turbine blade.